Overview of stunting conditions in Dusun Bolodog Tasikmalaya Regency - Ajda Firasyan Shiddiq; Oryza Nur Septia (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Stunting has become a national problem in almost all regions of Indonesia. Tasikmalaya Regency is one of the areas with a high percentage of stunting in West Java Province. Thematic KKN Si Penting is a community service program implemented by universities as an implementation of the Tri Dharma of Higher Education. This activity is an effort by universities to contribute to preventing stunting in the community. This community service aims to provide knowledge related to stunting to the community and analyze the conditions in the Bolodog Hamlet area of Tasikmalaya Regency. Socialization is a method used in distributing materials, and observations and surveys are carried out to analyze the conditions of mothers and children, namely by distributing questionnaires. The questionnaire was distributed to 15 mothers as respondents, and directions were given by students as facilitators. The survey results showed that overall, the stunting conditions in the Bolodog hamlet area were relatively low through an analysis of the results of each question from the questionnaire, with the majority of participants having maintained or improved conditions for children and their environment to create an anti-stunting environment.   Abstrak Stunting telah menjadi masalah nasional yang terjadi di hampir seluruh wilayah di Indonesia. Kab. Tasikmalaya menjadi salah satu daerah yang memiliki persentase stunting yang tinggi di Provinsi Jawa Barat. KKN Tematik Si Penting adalah program pengabdian yang dilaksanakan oleh perguruan tinggi sebagai implementasi dari Tri Dharma Perguruan Tinggi. Kegiatan ini menjadi upaya perguruan tinggi untuk berkontribusi dalam turut serta melakukan pencegahan stunting di masyarakat. Pengabdian ini bertujuan untuk memberikan pengetahuan terkait stunting kepada masyarakat serta menganalisis kondisi yang ada di daerah Dusun Bolodog Kab. Tasikmalaya. Sosialisasi menjadi cara yang dilakukan dalam pembagian materi, dan observasi serta survei dilakukan untuk analisis kondisi ibu dan anak yakni melalui pembagian angket. Angket dibagikan kepada 15 ibu sebagai responden disertai dengan arahan dari mahasiswa selaku fasilitator. Hasil survei menunjukkan bahwa bahwa secara keseluruhan, kondisi stunting di daerah dusun Bolodog sudah relatif rendah, melalui analisis hasil masing-masing pertanyaan dari angket dengan mayoritas partisipan telah menjaga atau memperbaik kondisi bagi anak dan lingkungannya agar menciptakan lingkungan yang anti stunting. Kata Kunci: anak usia dini; perkembangan motorik; sosialisasi; stunting